Developmental Readiness in the Understanding of Own and Other's False Beliefs. (13th October 2014) - Amadó, Anna; Serrat, Elisabet; Sidera, Francesc
Abstract : One of the most important milestones in the development of theory of mind is the understanding of false beliefs. This study compares children's understanding of representational change and others' false beliefs and evaluates the effectiveness of an appearance-reality training for improving children's false belief understanding. A total of 78 children ranging in age from 41 to 47 months were trained in three sessions and evaluated in a pretest and in a posttest. The results show that for children it is easier to understand representational change than false beliefs in others, and that the improvement after training was greater when starting from a higher score in the pretest. The implications of this for training in false belief understanding are discussed.